Eksplorasi Metode Nashar dalam Meningkatkan Kualitas Pembelajaran Nahwu Sharaf di Pondok Pesantren Assalafi Al Fithrah Surabaya - Sholihin, Choirus (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The study of Nahwu and Sharaf is a critical component in understanding the kitab kuning (classical Islamic texts) within Salafiyah Islamic boarding schools. This research explores the implementation of the Nashar method at Pondok Pesantren Assalafi Al Fithrah Surabaya as an innovative solution to enhance the quality of Nahwu and Sharaf learning. Designed with a simplified approach using Indonesian and enriched with song-based nadzam (mnemonics), the Nashar method aims to facilitate beginners in mastering the material. This study employs a qualitative descriptive approach, utilizing observation, interviews, and documentation for data collection. The findings reveal that the Nashar method effectively improves students' ability to read kitab kuning, supported by syllabus-based planning, structured implementation, and evaluation through assignments and examinations. However, obstacles such as low student motivation and limited teacher competence need to be addressed. The primary supporting factor is the creative integration of educational songs in the learning process. This research highlights the significance of innovative teaching methods in improving the educational quality in Islamic boarding schools